In Memory of Prof. Dr. Yuri V. Mitrishkin (1946–2024) - Artem E. Konkov; Pavel S. Korenev; Valerii I. Kruzhkov; Evgeniia A. Pavlova (Mathematics, 2024)
On 22 January 2024, at the age of 78, Yuri Vladimirovich Mitrishkin (Figure 1), an outstanding scientist and remarkable educator with half a century of experience, passed away unexpectedly [...]